Performance investigation of a rubber V-belt mini-CVT [compact disc] - 279090 Mohd. Yusrizal Bakri (Skudai : Universiti Teknologi Malaysia, 2005)
Project paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2005